Pengaruh Inflasi, PDRB, dan Tingkat Upah terhadap Penyerapan Tenaga Kerja pada Sektor Industri Pengolahan di Kota Banjarmasin - Athirah, Nur; Sa’roni, Chairul (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to determine the effect of Inflation, GRDP, and Wage Levels on Labor Absorption in the Manufacturing Sector of Banjarmasin City. This study uses secondary data from the Central Bureau of Statistics and related offices in the form of time series data from 2005 to 2017, with the object of research being the Banjarmasin City processing industry. Consists of inflation data for the City of Banjarmasin, the GRDP of the manufacturing sector at constant prices according to the field of business, the level of wages or minimum wages that apply in the City of Banjarmasin, as well as the workforce absorbed or working in the manufacturing sector of the City of Banjarmasin. The data analysis technique used is multiple linear regression analysis, whichitestss classical assumptions andses. The study results indicate that the three independent variables simultaneously have a positive and significant effect on employment. While partial inflation has a significant positive impact on work, GRDP and wage levels have an insignificant negative effect on labor absorption. The most influential variable on outcome is the inflation variable.